Hubungan otitis media supuratif kronis disertai kolesteatom dengan gangguan pengecapan - Lusiana Herawati Yammin; Joseph Bambang Soemantri; Lukmantya - (PERHATI-KL, 2013)
Background: Chorda tympanic nerve runs through the middle ear between the long crus of the incus andmanubrium of the mallei. Chorda tympanic nerve supplies the front two-thirds of the tongue taste. Many studieshad reported about gustatory alteration caused by ear surgery, but there were only small numbers of study aboutthis alteration in chronic otitis media (COM) patients prior to surgical treatment. Purpose: To find out whether theCOM patient with cholesteatoma have taste alteration or not, to investigate the relationship between COM withcholesteatoma (cholesteatoma level) to gustatory disorder (gustatory level) and the taste alteration in COMpatients with cholesteatoma before and after mastoidectomy surgery. Method: This was an analytic observationalstudy with cross sectional design. Sampling method was accidental sampling that involved 18 patients. Gustatoryfunction before and after surgery was examined using a taste strip test. Statistical analysis used in this study wasSpearman correlation test and Repeated ANOVA test. Results: Subjectively there was no taste disorder complaintamong these patients, although objectively there were patients that had taste disorder. The highest taste disordersfound in this study was hipogeusia (55,56%) followed by ageusia (22,22%) and normal taste (22,22%). Spearmancorrelation test between COM with cholesteatoma (cholesteatoma level) to gustatory disorder (gustatory level) wasp<0,05 and r=-0,543. Repeated ANOVA test taste alteration in COM patients with cholesteatoma before and aftermastoidectomy surgery was p >0,05. Conclusion: Most of COM patients with cholesteatoma had alteration of tasteprior to surgery. There was significant correlation between cholesteatoma level to gustatory disorder and thehigher cholesteatoma level,the lower the gustatory level. Statistically there was no significant differences gustatoryfunction in COM patients with cholesteatoma before and after surgery.Keywords: COM patient with cholesteatoma, gustatory, surgery. ABSTRAKLatar belakang: Nervus korda timpani berjalan melalui telinga tengah di antara prosesus longus inkus danmanubrium malei. Nervus korda timpani mempersarafi pengecapan dua pertiga depan lidah. Banyak penelitian tentangperubahan pengecapan akibat operasi telinga tengah, tetapi sedikit penelitian tentang perubahan pengecapan padapenderita otitis media supuratif kronis (OMSK) sebelum operasi. Tujuan: Mengetahui ada tidaknya penderita OMSKdengan kolesteatom yang mengalami gangguan pengecapan, adanya hubungan antara OMSK dengan kolesteatom(tingkat kolesteatom), gangguan pengecapan (tingkat pengecapan) dan ada tidaknya perubahan pengecapan padapenderita OMSK dengan kolesteatom sebelum dan setelah operasi mastoidektomi. Metode: Penelitian merupakanpenelitian observasional analitik dengan pendekatan cross sectional. Pengambilan sampel menggunakan teknikaccidental sampling melibatkan 18 penderita OMSK dengan kolesteatom. Pemeriksaan fungsi pengecapan dilakukansebelum dan setelah operasi menggunakan tes strip pengecapan. Analisis statistik menggunakan uji korelasi Spearmandan uji Repeated ANOVA. Hasil: Penderita OMSK dengan kolesteatom secara subjektif tidak mempunyai keluhanperubahan pengecapan, meskipun secara objektif penderita ada yang mengalami gangguan pengecapan. Hipogeusiamenempati proporsi terbanyak (55,56%) diikuti oleh ageusia (22,22%) dan pengecapan normal (22,22%). Hasil ujikorelasi Spearman antara OMSK dengan kolesteatom (tingkat kolesteatom) terhadap gangguan pengecapan (tingkatpengecapan) yaitu p < 0,05 dan r = -0,543. Hasil uji Repeated ANOVA pengecapan penderita OMSK dengankolesteatom sebelum dan setelah operasi mastoidektomi yaitu p>0,05. Kesimpulan: Sebagian besar penderita OMSKdengan kolesteatom telah mengalami penurunan pengecapan. Didapatkan hubungan bermakna antara tingkatkolesteatom dan tingkat (gangguan) pengecapan. Semakin tinggi tingkat kolesteatom pada penderita OMSK semakinmenurun tingkat pengecapan. Secara statistik tidak ada perbedaan bermakna perubahan pengecapan penderita sebelumdan setelah operasi.Kata kunci: OMSK dengan kolesteatom, pengecapan, operasi.